Operationalizing the distribution of oral HIV self-testing kits to men who have sex with men (MSM) in a highly homophobic environment: the Nigerian experience - Adekemi Sekoni; Waimar Tun; Osasuyi Dirisu; Temitope Ladi-Akinyemi; Elizabeth Shoyemi; Sylvia Adebajo; Folasade Ogunsola; Lung Vu (BMC, 2022)
Abstract Background Self-care health interventions are innovative approaches for improving health and achieving the sustainable development goals (SDGs). Men who have sex with men (MSM) have been disproportionately affected by Human Immunodeficiency Virus (HIV). In spite of this, stigma from healthcare workers has reportedly prevented MSM from accessing HIV testing in health facilities. This paper explored the operationalization of using key opinion leaders (KOLs) to distribute HIVST (HIV self-test) kits to MSM. This qualitative survey used a combination of in-depth interviews (IDI) with HIVST users and focus group discussions (FGDs) with KOLs to collect data three months after the distribution of the test kits by the KOLs. Thematic analysis of the data was carried out. Result Three themes were generated namely: KOLs serve as a trusted resource to promote and support HIVST for the MSM community; Skills and qualifications required for KOLs to effectively distribute and promote uptake of HIVST; and Effective strategies used to create demand and promote uptake of HIVST. Conclusion This study showed the practical steps involved in operationalizing KOL support system distribution of HIVST that positively influenced the testing experience for the participants irrespective of the HIV status and engagement in care. KOLs are a reliable resource to leverage for ensuring that HIV self-test kit is utilized and HIV positive individuals are linked to treatment and care in homophobic environments.